Challenges in XPS Analysis of PEO-LiTFSI-based Solid Electrolytes:How to Overcome X-ray-Induced Photodecomposition - Yusim, Yuriy; Moryson, Yannik; Seipp, Kevin; Sann, Joachim; Henss, Anja; Justus Liebig University Giessen (My University, 2024)
The cycle life of poly(ethylene oxide) (PEO) batteries containing lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is hindered by interfacial (electro)chemical electrolyte decomposition, a process traditionally examined via X-ray photoelectron spectroscopy (XPS). Our research presents a critical examination of X-ray induced photodecomposition, commonly misinterpreted as (electro)chemical electrolyte decomposition, in PEO-LiTFSI systems and those with NCM cathodes. We provide novel insights into this X-ray induced photodecomposition process and show that it is particularly pronounced when LiTFSI is dissolved and not in its pure state. Most importantly, we reveal that cryogenic measurement conditions can almost completely mitigate this photodecomposition. This insight not only deepens the understanding of photodecomposition within XPS analyses but also provides a transformative approach to the accurate characterization of electrolyte materials in lithium batteries.
Keywords: ddc:540